Estudos sobre as defasagens de Prometeu e Pandora - Santana, Thamiris de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Observational data collected in 1995 during the passage of the Earth by the ring plane of Saturn indicated angular lags in the predicted positions of Prometheus and Pandora. Using additional data these lags were confirmed, with Prometheus being about -19º of their estimated longitude and Pandora about 25º. A possible chaotic relationship due to a 121:118 mean motion resonance between the two satellites is currently accepted to explain those lags (Goldreich & Rappaport 2003b). However, an alternative work analyses the temporal evolution of the satellites semi-major axes and suggests that these lags are the result of non-ideal initial data which corresponds to a particular time and do not represent the behavior of satellites most of the time (Cruz 2004). In this work, we reanalyzed the lags of Prometheus and Pandora through a detailed study of the two aforementioned papers, testing analytically and numerically their main results. The results indicate that the observed lag originate from an initial condition corresponding to the time alignment of anti-periapses orbital of the satellites, once their are related by the 121: 118 mean motion resonance, they generate lags. It is proposed a way to measure the mass of the F-ring, which is still unknown, from the dynamic model developed in this work, resulting in an excessively large mass of the upper limit to be considered. In addition, from a study of the angular momentum conservation, we measure new densities for Prometheus and Pandora as [0:85 - 0:99]g cm-³ and [0:62 - 0:85]g cm-³, respectively

Dados observacionais obtidos em 1995 durante a passagem da Terra pelo plano dos anéis de Saturno indicaram defasagens angulares nas posições previstas de Prometeu e Pandora. Usando dados adicionais as defasagens foram confirmadas com Prometeu cerca de -19º de sua longitude prevista e Pandora cerca de +25º. Uma possível relação caótica provocada pela ressonância 121:118 de movimento médio entre os dois satélites é atualmente aceita para explicar essas defasagens (Goldreich & Rappaport 2003b). Entretanto, um trabalho alternativo que analisa as evoluções temporais dos semieixos maiores dos satélites propõe que essas defasagens são consequência de dados iniciais não ideais que pertencem a um momento muito específico e não representam o comportamento dos satélites a maior parte do tempo (Cruz 2004). Neste trabalho reanalisamos as defasagens de Prometeu e Pandora por meio do estudo detalhado dos dois trabalhos citados, testando analítica e numericamente seus principais resultados. Os nossos resultados indicam que as defasagens observadas são originarias da utilização de uma condição inicial do momento de anti-alinhamento dos periapses orbitais dos satélites, que uma vez relacionados pela ressonância 121:118, geram as defasagens. É proposta uma maneira de mensurar a massa do anel F a partir do modelo dinâmico desenvolvido no trabalho, que resultou em um limite superior de massa demasiadamente grande para ser considerado. Além disso, partindo de um estudo da conservação angular, mensuramos novas densidades para Prometeu e Pandora de [0; 85 - 0; 99]g cm-³ e [0; 62 - 0; 85]g cm-³,respectivamente
Studies about the lags of Prometheus and Pandora
Keywords: Satelites; Saturno (Planeta); Satelites - Orbitas; Ressonancia; Longitude; Satellites